Multidisciplinary Treatment: Follow-Up of Dental Autotransplantation for 10 Years - Camargo, Elisa Souza; Silva, Rhafaela Ribeiro; Rodrigues, Ádelin Olívia Lopes Joly; Andreis, Patricia Kern Di Scala; Maciel, José Vinicius Bolognesi; Luczyszyn, Sônia Mara; de Souza, Evelise Machado; Carneiro, Everdan; Vanzela, Nathália Juliana; Carlini, João Luiz (European Journal of Dentistry, 2024)
The objective is to present a clinical case of dental autotransplantation managed with surgery, orthodontics, endodontics, periodontics, and aesthetic rehabilitation. A 10-year-old boy sought treatment after avulsion of the maxillary left central incisor, which was not reimplanted. Based on anamnesis, clinical examination, and complementary examinations, agenesis of the maxillary and mandibular second premolars except the mandibular right second premolar was observed. After a multidisciplinary planning, the space in the maxillary left central incisor region was opened to receive the transplanted mandibular right second premolar. The receptor site was created in a single surgical procedure. Pulp necrosis was noted in the transplanted tooth, which was treated endodontically, and the agenesis spaces were closed using fixed orthodontic appliances. After removing the appliance, gingivectomy with osteotomy was performed in the maxillary right central incisor and the transplanted tooth regions to harmonize the height and shape of the gingival contour. Next, aesthetic readjustment was performed with tooth whitening, using office and home techniques, followed by microabrasion of the vestibular surface of the maxillary right central incisor. Direct composite resin restorations were placed in the maxillary incisors, and the teeth were rehabilitated using incisal and palatal guides. A multidisciplinary approach is essential for reestablishing the function and aesthetics of complex cases involving dental autotransplantation.
Keywords: autotransplant; tooth avulsion; multidisciplinary care team